The trajectory of head circumference and neurodevelopment in very preterm newborns during the first two years of life: a cohort study - Maria Luciana de Siqueira Mayrink; Letícia Duarte Villela; Maria Dalva Barbosa Baker Méio; Fernanda Valente Mendes Soares; Andrea Dunshee de Abranches; Sylvia Reis Gonçalves Nehab; Ana Beatriz Rodrigues Reis; Leticia Baptista de Paula Barros; Maura Calixto Cecherelli de Rodrigues; Saint-Clair Gomes Junior; Maria Elisabeth Lopes Moreira (Elsevier, 2024)
Objective: To evaluate the growth trajectory of head circumference and neurodevelopment, and to correlate head circumference with cognitive, language, and motor outcomes during the first two years. Method: Prospective cohort study in a tertiary hospital including 95 newborns under 32 weeks or 1500 g. Neonates who developed major neonatal morbidities were excluded. The head circumference was measured at birth, at discharge, and at term-equivalent age, 1, 3, 5, 12, 18, and 24 months of corrected age, and the Bayley Scales (Bayley-III) were applied at 12, 18 and 24 months of corrected age to assess cognitive, language and, motor domains. Scores below 85 were classified as mild/moderate deficits and scores below 70 as severe deficits. The association between head circumference Z score and Bayley scores was assessed using Pearson's correlation. The study considered a significance level of 0.05. Results: There was a decrease of -0.18 in the head circumference Z score between birth and discharge and the catch-up occurred between discharge and 1 month (an increase of 0.81 in the Z score). There was a positive correlation between head circumference and Bayley scores at 18 months. There was also a positive correlation between head circumference at discharge and at 5 months with the three domains of the Bayley. Conclusion: Serial measurements of head circumference provide knowledge of the trajectory of growth, with early catch-up between discharge and 1 month, as well as its association with neurodevelopment. Head circumference is therefore a valuable clinical marker for neurodevelopment, especially in very preterm newborns.